루이사 발렌수엘라의 ｢이것이 인생이라면, 나는 빨간 망토 소녀｣에 나타난 여성의 섹슈얼리티 자각을 통한 가부장적 이데올로기의 해체 - 최은경(Choi, Eun-kyung) (외국문학연구, 2024)
본 연구는 아르헨티나 포스트 붐 작가 루이사 발렌수엘라 Luisa Valenzuela (1938― )의 단편소설 「이것이 인생이라면, 나는 빨간 망토 소녀 Si esto es la vida, yo soy Caperucita Roja」 (1993)에 나타난 여성의 섹슈얼리티 자각과 그를 통한 가부장적 이데올로기의 해체 과정을 분석한다. 본 연구는 우선 여성의 목소리로 여성 자신의 섹슈얼리티를 탐구하는 서사를 여성 중심적 글쓰기의 사례로 해석한다. 이후 본고는 작품 속 주인공의 섹슈얼리티 자각이 타자에 대한 이해로 확장되는 과정과, 이러한 내면 탐구가 타인과의 소통과 관계 형성에 새로운 패러다임을 제시하는 양상을 고찰한다. 특히 본 연구는 여성의 섹슈얼리티 자각이 가부장제를 내면화하고 전파하는 가부장적 여성성의 해체로 이어지는 과정을 조명하며 이것이 가부장적 이데올로기 해체의 실마리가 될 수 있음을 분석한다. 이렇게 본 논문은 발렌수엘라의 「이것이 인생이라면, 나는 빨간 망토 소녀」에서 「빨간 망토」의 개작본에 축적된 가부장적 이데올로기가 어떻게 해체되는지를 분석한다. 궁극적으로 본 연구는 발렌수엘라의 동화 개작이 여성을 가부장적 사고방식의 전달자이자 타 여성 억압의 도구로 삼았던 가부장적 이데올로기를 해체하기 위해, 여성의 섹슈얼리티를 전략적이고 핵심적인 기제로 선택했음을 논증한다. This study explores the dismantling of patriarchal ideology through women’s awareness of their own sexuality, as portrayed in Argentine post-boom writer Luisa Valenzuela (1938-)’s short story, “If This Is Life, I’m Red Riding Hood Si esto es la vida, yo soy Caperucita Roja” (1993). If first asserts that Valenzuela’s narrative, which depicts a female journey of sexual awareness through a female voice, examplifies gynocritical writing. Then it examines how the protagonist's growing awareness of her sexuality fosters a deeper understanding of the Other, suggesting that self-exploration contributes to improved communication and relationships. Additionally, this study analyzes how a women's recognition of her own sexuality enables the deconstruction of femininity as an internalized vehicle of patriarchy, ultimately signaling a liberation from patriarchal constraints. Thus, this study demonstrates how Valenzuela’s transformation of “Little Red Riding Hood” into “If This Is Life, I’m Red Riding Hood” emphasizes female sexual awareness as a key mechanism for dismantling the patriarchal ideology inherent in traditional fairy tales. In this way, this paper analyzes how patriarchal ideologies accumulated in the adaptation of Little Red Riding Hood are deconstructed in Valenzuela's “If This Is Life, I’m Red Riding Hood.” Ultimately, this study argues that Valenzuela's rewriting of a fairy tale chose female sexuality as a strategic and central device to deconstruct patriarchal ideologies that positioned women as carriers of patriarchal ideas and instruments of oppression of other women. KCI Citation Count: 0